(untitled) (Research, Society and Development, 2021)
Generalized anxiety disorder (GAD) is characterized by chronic excessive worry followed by symptoms such as restlessness, irritability, fatigue, sleep disturbance, muscle tension and/or difficulty concentrating. Benzodiazepines (BZDs), until a few years ago considered the only class of medication used for GAD, are still present in current treatments, because, when compared to other anxiety medications, they seem to be more effective in the somatic symptoms of the disease. The great concern about the use of this pharmacological class is the potential of causing dependence and tolerance, especially when used incorrectly. This is a study carried out by means of exploratory-descriptive research, qualitative-quantitative approach. The survey was conducted in October 2021, with customers of a drugstore, located in the city of Vitória da Conquista (BA). As an instrument of data collection, an online questionnaire was used with the objective of analyzing the impacts of benzodiazepine medications on the quality of life of people with generalized anxiety disorders. Forty-two people were interviewed, with a prevalence of females (76.2%). The participants of the study defined as the main side effects of the treatment: excessive sedation (21.6%), dependence (19%), lethargy (16.7%), decreased reflexes (13.8%), and tolerance (12.6%). When asked about the benefits generated after starting treatment with BZDs, 47.6% of the participants defined the decrease in anxiety symptoms as the main benefit, while 35.7% set quality of sleep as most important and another 16.7% revealed the quick start of action as the most relevant positive effect. Therefore, the data collected in this study demonstrate that benzodiazepines have both positive and negative impacts on the quality of life of those with GAD, but when used correctly, the benefits of these drugs can overcome the risks.